The Effectiveness of Contextual Teaching and Learning (CTL) and Project Based Learning (PJBL) Methods on Student Learning Outcomes - M. Anwarul Haq Al Fawaas; Zamzam Mustofa; Rihab Wit Daryono (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This research aims to assess the effectiveness of the Project-Based Learning (PJBL) method on student achievement in the Aqidah Akhlak subject in class X at Ma Ma'arif Balong. Method: The research method was a quasi-experiment with a pretest-posttest control group design. The research sample consisted of two classes: one class as experimental group 1, which received Aqidah Akhlak learning using the Contextual Teaching and Learning method, and one class as experimental group 2, which received learning Aqidah Akhlak using the Project Learning method. Data was collected through test instruments covering various aspects of the learning material of class X. Results: The research results were analyzed using descriptive and inferential statistical analysis techniques. The analysis results show that students who study using the PJBL method significantly increase their learning achievement compared to students who use the conventional method, which only reaches 48.20%. Students involved in PJBL learning show a better understanding of concepts, applying moral values, and problem-solving abilities. Novelty: This research contributes to strengthening empirical evidence regarding the effectiveness of the PJBL method in improving student learning achievement in the Aqidah Akhlak subject. The implication is that innovative and interactive learning approaches such as PJBL must be implemented to improve the quality of Islamic learning at the upper secondary level. Researchers hope that the results of this research can provide valuable contributions to teachers, schools, and other educational stakeholders to improve learning approaches in the future.